Дневник Домового - Чеширко Евгений (Одобрено Рунетом, 2018)
Экземпляры: Шольинская библиотека (20191120) / Инвентарный номер: 8079 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ч-57 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6